NEURAL SIGNALS UNDERLYING COORDINATE FRAME OF ATTENTION IN AREA 7a OF PRIMATE POSTERIOR PARIETAL CORTEX - Rawley, Justin (Wake Forest University, 2009)
The posterior paritetal cortex is recognized as an association area that amalgamates sensory information and transforms it into signals enabling the coordination of motor actions. The allocation of visual attention is a necessary part of this process and posterior parietal area 7a is one of the main areas thought to mediate it. When 7a is compromised, disruptions such as visual neglect and apraxia can result. While evidence exists that 7a encodes sensory signals in world centered coordinates, the reference frame of visual attention was previously unknown. We observed that while some elements of 7a encoding are malleable dependent upon behavioral context, the reference frame of attention is also predominantly encoded in a world-referenced system. We also find that the electrophysiologically defined pyramidal and interneuron subtypes participate in approximately equal proportions in the 7a networks that mediate both visual attention and working memory.
Keywords: Parietal Cortex; Area 7a; Primate; Visual attention